EVALUATING THE SUCCESS RATE OF VAGINAL DELIVERY AFTER CAESAREAN SECTION - MEHWISH, .; NAFEES, S; KUNBAHAR, T; PARVEEN, T; IQBAL, M; NAFEES, S (Biological and Clinical Sciences Research Journal, 2023)
: The retrospective study was conducted in the Department of Gynecology Dr. Ruth K. M. Pfau Civil Hospital Karachi, from February 2021 to February 2022, for the evaluation of factors associated with the success of TOLAC (trial of labor after cesarean delivery) and to identify variables for predicting the success of TOLAC in subjects with prior Caesarean section (CS). A total of 315 women were included in the study. They were divided into the validation cohort (n=20, 63%) and the training cohort(n=295, 93.6%). The primary endpoint was the success rate of vaginal delivery. The results showed that of 315 participants, 264 (83.8%) women had successful TOLAC and vaginal delivery, and 51 (16.1%) had ERCS. According to multivariate analysis, BMI-estimated birth weight, gestational age <41 weeks, rupture of membranes, and cervix Bishop score ≥5 was significantly associated with the success of TOLAC. Results suggest that TOLAC has a high success rate in women with a history of c-sections.